A known mutation in GJB6 in a large Chinese family with hidrotic ectodermal dysplasia. (3rd May 2016) - Yang, R.; Hu, ZL.; Kong, QT.; Li, WW.; Zhang, LL.; Du, X.; Huang, SY.; Xia, XY.; Sang, H.
Abstract: Background: Hidrotic ectodermal dysplasia (HED), also named as Clouston syndrome, is a rare autosomal dominant disease. Mutations in GJB6, GJB2 and GJA1 are related to HED. Objective: Summarize the clinical feature and analyse the mutation of the GJB6 gene in a large Chinese family with HED. Methods: We collected a very large Chinese family with HED. Clinical information was analysed. Blood samples were obtained. The whole coding region of GJB6 was amplified by polymerase chain reaction and sequenced. The results were further confirmed at mRNA level by reverse transcription polymerase chain reaction. Results: Sequence analysis identified a heterozygous missense mutation c.263C>T (p.A88V) in genomic DNAs of 25 patients, and this mutation was excluded from 14 normal individuals in this HED family and 218 unrelated, population‐matched control individuals. The transcription of mutated allele was confirmed by RT‐PCR of Cx30 mRNA from proband, s scalp skin. We found a novel phenotype of this variant in this Chinese HED family. Conclusion: Our data reveals that a recurrent mutation p.A88V in GJB6 played a pathogenic role in a large Chinese family and emphasizes the importance of gene test in this congenital disorder.